SOFT SKILLS TRAINING TO IMPROVE THE QUALITY OF EDUCATIONSERVICES AND TEACHER SOFT SKILLS MANAGEMENT TO STRENGTHEN THE QUALITY OF LEARNING - Hari Kurniawanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
One effort to improve the quality of education is to improve the quality of educational institutions. In an effort to improve the quality of educational institutions, we do not only fulfill the input and output aspects, but what is more important is the process aspect. Starting from making a decision, managing the planned program, the management process, the process of teaching and learning activities and the process for monitoring and evaluation. In this context, the learning process has the highest level of significance when compared with other processes (Sum & Taran, 2020). The success of the learning process is always closely tied to the quality of the teacher as the main actor. Therefore, a qualified teacher is needed in an effort to improve the quality of the institution Soft skills management is very important for education teachers so that it will have an impact on improving the quality of educational institutions and can have a direct impact on teachers. In order to support the achievement of institutional quality, teachers should always hone and optimize their soft skills. These include communication, interpersonal skills, team building, critical thinking, positive attitudes, establishing relationships with students, parents and the community. In future research, further study is needed regarding soft skills management for teachers with various individual and institutional backgrounds in order to improve the quality of education.